If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * 6 + 94 + -76 = 31 Reorder the terms for easier multiplication: 6x + 94 + -76 = 31 Reorder the terms: 94 + -76 + 6x = 31 Combine like terms: 94 + -76 = 18 18 + 6x = 31 Solving 18 + 6x = 31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 6x = 31 + -18 Combine like terms: 18 + -18 = 0 0 + 6x = 31 + -18 6x = 31 + -18 Combine like terms: 31 + -18 = 13 6x = 13 Divide each side by '6'. x = 2.166666667 Simplifying x = 2.166666667
| 9-(4y-21)=1-5y | | 0.3-0.9ln(x+1)=0 | | 10x+3=5x+18 | | 2t-11=23 | | 5n-5=11-n | | 6x+2(-6)=12 | | -7x-2x=18 | | 5=13 | | 5(2x+8)=-20+10 | | 5-2(4a+1)+3a= | | 6x+2(0)=12 | | (8+z)(2z-3)=0 | | 5(x+5)=5(x-5) | | 7x+9=71+x | | 5x-2=14x-38x | | -10x+4=-186 | | 5+49x=28x+17 | | (8a^5+6b)+-5a^5= | | 6(-4+x)=-42 | | 4+n=16 | | 2y-3=1.2-y | | 252=18n | | 5x+6x^2=5 | | (x+3i)(x+3i)= | | 5ln(x+3)=10 | | (x-y)dx+(x+y)dy=0 | | r/5=12/5 | | 9n+11=41-6n | | 4(x+2)-7=2x+2(2+x) | | 13=n/16 | | 38-18=4(x-2) | | -13=m+5 |